Geo-special Community Analysis on The Knowledge, Attitude and Practice of Preventive Measures Adopted in Response to Cases of Resurgent Malaria by The Populations of The Provinces of Maniema and Kwango in the Democratic Republic of Congo - Priss, Tambwe Mwabi; Bonny, Assani Wakenge; Alphonse, Masandi Milondo; John, Kahozi Mihali; Désiré, Kibonge Pascal; Jeanne d’Arc, Iragi Mundinga; Placide, Mbungi Pangalala (British Journal of Healthcare and Medical Research, 2024)
Malaria remains a public health problem in the Democratic Republic of Congo, despite the interventions and recommendations of the National Malaria Control Programme. The aim of this study was to analyse the knowledge and preventive measures adopted by the population of Maniema and Kwango provinces in the face of resurgent malaria. It was a case-control study based on retrospective questioning of hospitalised people of both sexes (the warders). The data were analysed using SPSS version 26 softwares. People in Maniema and Kwango provinces have a good knowledge of malaria, the causal agent and the mode of transmission. To combat the resurgence of cases of malaria in their households, they have taken appropriate action, such as going to the health centre and/or hospital for treatment in the event of illness or even giving malaria medication at home, cleaning up their environment and getting into the habit of sleeping under an insecticide-impregnated mosquito net.